Поширення альфвенових хвиль та перенесення енергії поперек магнітних поверхонь у тороїдальній плазмі - Тищенко, Маргарита Германівна; Tyshchenko, M.H. (Харків: Харківський національний університет імені В.Н. Каразіна, 2021)
Tyshchenko M.H. Propagation of Alfvén waves and energy transfer across magnetic surfaces in toroidal plasmas. – Manuscript. Thesis for the Candidate of Science (Doctor of Philosophy) degree in Physics and Mathematics, speciality 01.04.08 – Plasma Physics. – Institute for Nuclear Research, National Academy of Science of Ukraine; V. N. Karazin Kharkiv National University, the Ministry of Education and Science of Ukraine, – Kharkiv, 2021. This dissertation is devoted to current problems of the physics of magnetohydrodynamic waves in toroidal fusion devices. It presents results of theoretical investigation of physics of the transverse energy transfer by Alfvén waves and magnetic islands, and of effects of the spatial chanelling of the energy of energetic ions/alpha particles by destabilized Alfvén eigenmodes in tokamaks. The developed theory is applied to experimental data from the spherical torus NSTX (USA) and tokamak JET (United Kingdom). It is demonstrated that toroidicity (as well as ellipticity and other kinds of deviations of the magnetic configuration from the cylindrical geometry) can result in linear transformations of propagating kinetic Alfvén waves (KAWs) into other KAW branches, which differ by their mode numbers from the initial waves. Analytical expressions for the amplitudes of the transformed and non-transformed waves are derived. The transformation is found to be strong for kinetic Alfvén waves with low poloidal mode numbers in typical tokamaks, NSTX and ITER (France). It may affect the mode numbers observed by external magnetic measurements and weaken the Landau damping of the waves, thus extending the region of the wave propagation. The latter can be important when the wave affects the plasma energy balance transferring the energy or modifying the plasma transport coefficients.
Propagation of Alfvén waves and energy transfer across magnetic surfaces in toroidal plasmas
В дисертації проаналізовано зміни модової структури кінетичних альфвенових хвиль при їх поширенні поперек тороїдного магнітного поля. Отримано аналітичні вирази для амплітуд трансформованої і нетрансформованої хвиль. Показано, що трансформація може бути сильною для хвиль з малими полоїдальними номерами мод, зокрема в таких термоядерних пристроях як NSTX (США) та ITER (Франція). Знайдено величину та розташування потоків частинок та енергії, що виникають при цеберному перенесенні внаслідок гальмування швидких йонів в полі квазістаціонарних збурень.
Keywords: токамак; енергійні йони; транспорт; резонансні острови; альфвенові хвилі; власні моди; нестійкості плазми; tokamak; energetic ions; transport; resonance islands; Alfvén waves; eigenmodes; plasma instabilities